Bone Morphogenetic Proteins and Bone Derived Growth Factors - Forell, Elaine B.; Straw, R. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Recent studies suggest that local control of bone homeostatic and reparative mechanisms is most likely attributable to the interrelated function of a number of bone morphogenetic proteins (BMP) and bone derived growth factors. While osteogenesis is believed to be initiated by BMP, bone growth factors are thought to play a role in the promotion and maintenance of the newly induced bone and in the regulation of normal bone remodeling and repair. An overview of the current literature pertaining to BMP and the various bone derived growth factors is presented.While osteogenesis is believed to be initiated by bone morphogenetic proteins, bone growth factors are thought to play a role in the maintenance of the newly induced bone and in the regulation of normal bone remodeling and repair. Current research suggests that, in the future, these substances may be used as systemic or locally administered adjuvant therapy in order to accelerate bone regeneration and fracture healing.
Keywords: Bone; growth factors; bone morphogenetic proteins